Real-world clinical treatment outcomes in Chinese non-small cell lung cancer with EGFR exon 20 insertion mutations - Shi, Chao; Xing, Ruyue; Li, Mengmeng; Feng, Junnan; Sun, Rui; Wei, Bing; Guo, Yongjun; Ma, Jie; Wang, Huijuan (Frontiers in Oncology, 2022)
Background: EGFR exon 20 insertions (EGFR ex20ins) constitute a heterogeneous subset of EGFR-activating alterations. However, the effectiveness of standard therapy in patients with EGFR ex20ins remains poor. Methods: In our study, we retrospectively collected next-generation sequencing (NGS) data from 7831 Chinese NSCLC patients, and analyzed the relationship between EGFR ex20ins variations and medical records. Results: Our data showed that EGFR ex20ins account for up to 3.5% of all EGFR mutation non-small-cell lung cancer (NSCLC) patients and 1.6% of all NSCLC patients in China. 38 different variants of EGFR ex20ins were identified in 129 NSCLC patients. We observed that the patients with EGFR ex20ins may benefit from the antiangiogenesis agents significantly (P=0.027). In EGFR ex20ins near loop group, patients received 2nd/3rd -generation EGFR-TKI therapy treatment as 1st-line treatment had longer median progression-free survival (PFS) than those initiated treatment with 1st-generation EGFR-TKI or chemotherapy. Patients with co-mutations of EGFR ex20ins near loop and TP53 tended to have shorter OS in 2nd/3rd-generation EGFR-TKI therapy (P=0.039). Additionally, median PFS was significantly longer in patients harboring EGFR ex20ins far loop variants received chemotherapy as a 1st-line setting (P=0.037). Conclusions: Overall survival was significantly longer in EGFR ex20ins patients with antiangiogenesis agents. For the choice of first-line strategy, NSCLC with EGFR ex20ins near loop variants may benefit from 2nd/3rd -generation EGFR-TKI, while patients harboring EGFR ex20ins far loop variants might have better outcomes from chemotherapy. TP53 could serve as a potential predictive marker in poor prognosis for EGFR ex20ins near loop patients.